(untitled) (Al-Academy, 2026)
In light of the rapid scientific developments and technological discoveries that have penetrated all fields of life, the theater has intended to employ them to keep pace with technological development, translating this interaction into digital technologies and light projections as visual processors that perform aesthetic and dramatic functions and multiple assumptions through the computer and other digital media that strengthened the visions of the director and designer and restored the communicative relationship with the recipient. The current research included four chapters: The first chapter, the methodological framework. This chapter included the research problem, as well as the importance of the research, the goal of the research, and the limits of the research. The chapter concluded by defining terms linguistically, terminologically, and procedurally. The second chapter, the theoretical framework, included: The first topic: digital technologies The second topic: Technical treatments for optical projection devices in shaping the theatrical performance space The third chapter included research procedures. While the research concluded with the fourth chapter, results, conclusions, recommendations and proposals.